High Literacy and Mounting Violence: A Case of Women in Kerala, India - Nithya N.R (International Journal of Scientific and Research Publications, 2013)
In this paper titled ‘High Literacy and Mounting Violence: A Case of Women in Kerala, India’, a modest attempt has been made to discuss the forms and types of violence against women. In all societies, to a greater or lesser degree, women and girls are subjected to physical, sexual and psychological abuse that cuts across lines of income, class and culture. It has been recognized as a violation of basic human rights of women and of their exercise of fundamental freedom. Why should violence against women be distinguished from other forms of violence? Because it has a global magnitude and it is based on sex inequality. It cuts across cultural and religious barriers, impeding the right of women to participate fully in society. Kerala, one of the most developed states of the country in terms of human development indices, is unfortunately no exception in the matter of crimes against women. Government and voluntary agencies are doing their level best to protect women and wipe out this negative indicator of development yet it continues to increase day by day. The paper also suggests remedial measures for preventing violence against women.